Elaboración de una bebida fortificada a partir de la variedad de amaranto INIAP alegría (Amaranthus caudatus l.) y la variedad de quinua INIAP tunkahuan (Chenopodium quinoa willd.) con tres concentraciones y tres tipos de endulzantes (estevia, panela y miel de abeja) para garantizar la seguridad alimentaria en la provincia de Cotopaxi, cantón Latacunga, parroquia Eloy Alfaro, sector Salache, laboratorios académicos de la carrera de ingeniería agroindustrial, en el periodo 2014-2015 - Mera Vizcaíno, Lizeth Patricia (2016)
The process of the fortified drink from the variety INIAP Alegria amaranth (Amaranthus caudatus L.) and the variety of quinoa INIAP Tunkahuan (Chemopodiam quinou Willd.) with three levels and three types of sweeteners (stevia, brown sugar and honey fly) it was as follows: the raw material receiving, sorting, soaking process of amaranth within two hours and desaponification of the quinoa, runoff, cooking (pressure cooker 40 minutes), liquefied, filtering, mixed, switer, flash pasteurization (80°C for 5 minutes with a thermal shock to 30°C), cooled, packaging, labeling and finally stored (2-4°C). The drink was subjected to sensory evaluation assessment where factors assessed were the color, taste, smell and acceptability showing the three better treatments which were t2 (50% amaranth + 50% quinoa + bround sugar), t5 (60% amaranth + 40% quinoa + bround sugar) and t8 (70% amaranth + 30% quinoa + bround sugar)….